1997
DOI: 10.1016/s0014-5793(97)01495-6
|View full text |Cite
|
Sign up to set email alerts
|

Ether lipid biosynthesis: isolation and molecular characterization of human dihydroxyacetonephosphate acyltransferase

Abstract: In this paper we describe isolation and molecular characterization of human dihydroxyacetonephosphate acyltransferase (DAP-AT). The enzyme was extracted from rabbit Harderian gland peroxisomes and isolated as a trimeric complex by sucrose density gradient centrifugation. From peptide sequences matching EST-clones were obtained which allowed cloning and sequencing of the cDNA from a human cDNA library. The nucleotide-derived amino acid sequence revealed a protein consisting of 680 amino acid residues of molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
56
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 35 publications
0
56
0
Order By: Relevance
“…The human DHAPAT cDNA (14) was removed from the pBluescript SK phagemid vector and inserted into the shuttle vector pBK-CMV (Stratagene, La Jolla, CA) using the Eco RI (5 Ј ) and Xho I (3 Ј ) restriction sites. The construct was used to transform XL1-Blue MRF Ј , which was then grown on kanamycin-containing agar to form colonies.…”
Section: Construction Of An Expression Vector Containing Human Dhapatmentioning
confidence: 99%
See 1 more Smart Citation
“…The human DHAPAT cDNA (14) was removed from the pBluescript SK phagemid vector and inserted into the shuttle vector pBK-CMV (Stratagene, La Jolla, CA) using the Eco RI (5 Ј ) and Xho I (3 Ј ) restriction sites. The construct was used to transform XL1-Blue MRF Ј , which was then grown on kanamycin-containing agar to form colonies.…”
Section: Construction Of An Expression Vector Containing Human Dhapatmentioning
confidence: 99%
“…Our lack of knowledge in this area is attributable, in part, to the lack of molecular tools for studying the system. Only recently have any of the enzymes that participate in the biosynthetic pathway for plasmalogens been purified or the genes that code for them cloned (14,15).…”
mentioning
confidence: 99%
“…Northern Blot Analysis of DHAPAT mRNA during Cell Differentiation-The human DHAPAT cDNA has been cloned (16,17) and a number of human and mouse EST clones are available. One EST clone (W54198) was used for Northern blot analysis of the DHAPAT mRNA in 3T3-L1 cells during differentiation.…”
Section: Differentiation-induced Increased Activity Of Lipogenic Enzymentioning
confidence: 99%
“…Novikoff and co-workers (4) reported that during differentiation of 3T3-L1 cells there is a large increase in the number of peroxisomes (catalase-containing organelles) and the amount of endoplasmic reticulum (ER), and in an abstract, they also reported that DHAPAT in differentiated 3T3-L1 cells was associated with peroxisomes (14). In light of our progress in purifying specific DHAPAT (15) and the recent cloning of its cDNA (16,17), we examined whether peroxisomal DHAPAT is induced during differentiation of these cells, along with the nonspecific microsomal GPAT, by studying the properties and subcellular distributions of the enzymes. The results indicate that peroxisomal DHAPAT and its mRNA are indeed induced during adipogenesis.…”
mentioning
confidence: 99%
“…In most animal tissues, DHAPAT is found in a membrane-bound fraction (15,20) and localized in the luminal side of peroxisomes (15,21). This enzyme was also found to be part of a heterotrimeric complex that includes the 1-alkyl-DHAP synthase (22,23). Alterations in DHAPAT function have been associated with various human diseases such as neonatal adrenoleukodystrophy, infantile Refsum, disease, hyperpipecolic academia, and rhizomelic chondrodyplasia punctata (24 -26).…”
mentioning
confidence: 99%